Collection of a List of Pseudo-Scientific or Unsupported Beliefs of Iranians about Oral Health: A Qualitative Study in 1399 - Fatemeh Rahmatzadeh; Elya ranayi; Saber Babazadeh; Ali Kazemian (Mashhad University of Medical Sciences, 2022)
Introduction: Harmful unhealthy behaviors could be rooted in common unsupported beliefs in communities. Therefore, this study aimed to compile a list of pseudo-scientific and unsupported beliefs of Iranians about oral health.Materials and Methods: The present study was a qualitative research project using an ethnography approach. First, the researchers extracted a list of the pseudo-scientific and unsupported beliefs of Iranians about oral health. These beliefs were defined as not being supported by the available scientific evidence. The following five methods were used for the extraction of these beliefs: 1) analysis of various relevant websites or social network channels; 2) search for written documents related to Iranian popular culture; 3) open-ended interviews with 35 patients of Mashhad Dental School (Mashhad, Iran), of different genders, ages, and education levels; 4) telephone conversations with Iranian practicing dentists; and 5) interviews with a purposive sample of 13 professors at Mashhad Dental School (Mashhad, Iran). Therefore, there were two target groups of the interviews, including dentists (the most important reference group in the field of oral health), and Iranian people from different social classes. The interviews continued until saturation was achieved. Afterward, the text of documents, sources, and interviews were analyzed to extract possible pseudo-scientific beliefs. Finally, these beliefs were categorized into several groups based on common themes.Results: In this ethnographic study, after removing duplicate and ambiguous themes, 181 statements were obtained, which were categorized into the following 11 groups, according to the common themes: actions are taken to prevent caries, factors that cause tooth decay, whitening teeth, toothache relief, treatment of infections, gums and related diseases, pregnancy, the oral health of children, mouth ulcers, tooth extraction, and other cases.Conclusion: Iranians have various beliefs about oral health that might be unsupported scientifically. The list gathered in this study needs to be completed in further studies.